ANALISIS EFISIENSI TEKNIS PERBANKAN DI INDONESIA - Dewi, Kartika; Siauwijaya, Rahmat (Jurnal Manajemen, 2016)
This research investigates the technical eficiency of the banks listed in Jakarta Stock Exchange in Indonesia from year 2009 to 2012. This research also compares the levels of technical efficiency between Bank Umum Milik Negara (BUMN), Bank Umum Swasta Nasional (BUSN) Devisa and Bank Umum Swasta Nasional (BUSN) Non Devisa by using non-parametric Data Envelopment Analysis (DEA). DEA was calculated using input orientation and variable return to scale. ANOVA is also applied to compare efficiency between banks. The sample was selected using purposive sampling of 33 banks listed in Jakarta Stock Exchange for period 2009-2012. The result of this study shows that BUMN is the most efficient banks compared to the BUSN Devisa and BUSN Non Devisa. Furthemore, BUSN devisa is the least efficient bank. Finally, this research found that there is a significant difference of the technical efficiency between the groups of banks.Keywords: Eficiency Technique, Banking, Data Envelopment Analysis